Injury-induced tau pathology promotes aggressive behavior in Drosophila without neurodegeneration - Roilea Maxson; Christine J. Smoyer; Megan F. Hampton; Yusheng Shen; Kailea Wiese; Cheryl Yee; Aishini Singh; Alexandria Funtila; Richard J. McKenney; Kassandra M. Ori-McKenney (Proceedings of the National Academy of Sciences, 2026)
The microtubule-associated protein tau is implicated in neurodegenerative diseases, but its physiological roles remain poorly understood. Here, we find that panneuronal expression of human tau (HsTau) in Drosophila coupled with injury triggers elevated aggression in male flies, which was not observed in flies expressing nonphosphorylatable tau. These behavioral manifestations result from activation of dopaminergic circuits without neurodegeneration. Using in vitro reconstitution assays, we find that phosphorylated HsTau maintains microtubule binding but loses its ability to suppress catastrophes, thereby promoting microtubule dynamicity. In contrast, unphosphorylated HsTau as well as fly tau (DmTau) stabilize microtubules by reducing catastrophe frequency. Our findings challenge the canonical view of tau as a simple microtubule stabilizer and instead position it as a dynamic regulator of microtubule function and neuronal excitability. These results reveal how acute tau phosphorylation can alter neural circuit function and behavior prior to neurodegeneration, providing insights into tau’s physiological and pathological roles.